2019
DOI: 10.1021/acs.jcim.9b00163
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Positions of Bridging Water Molecules in Nucleic Acid–Ligand Complexes

Abstract: Over the past two decades, interests in DNA and RNA as drug targets have been growing rapidly. Following the trends observed with protein drug targets, computational approaches for drug design have been developed for this new class of molecules. Our efforts toward the development of a universal docking program, FITTED, led us to focus on nucleic acids. Throughout the development of this docking program, efforts were directed toward displaceable water molecules which must be accurately located for optimal docki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Consequently, there are still many ongoing developments in FFs. [46][47][48][49][50] Finally, in the future, H-TEQ 4.0 should be further extended to be applicable to all dihedral angles. Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, there are still many ongoing developments in FFs. [46][47][48][49][50] Finally, in the future, H-TEQ 4.0 should be further extended to be applicable to all dihedral angles. Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…It is built on the most frequent interactions observed in crystal complexes [62]. Recently, methods like the 3D-RISM methods [60] or the SPLASH'EM scoring function [63] allowing waters and cations site-prediction during structure optimization aimed at addressing this challenging task. The accuracy of these methods still suffers from the limited number of nucleic acid-ligand solved 3D structures [63].…”
Section: Metal Ions and Solvationmentioning
confidence: 99%
“…Several high-resolution crystallographic studies of native GQs [112][113][114][115] and GQligand complexes [71,74,75,80,81,98,100,116,117] have reported that water molecules are intimately associated with GQ sites and with bound ligand. It is well-established for DNA-, RNA- [118], and protein-ligand complexes [119][120][121][122][123] that water molecules can play critical target-ligand mediation roles. The present work analyzes water arrangements in several GQ-ligand complexes (PDB id 3CE5, 3NZ7, and 3UYH) [74,81,100] that are of sufficient resolution to give confidence in the significance of the arrangements, to better understand the role and the consequences of discrete water molecules associated with ligand binding.…”
Section: Introductionmentioning
confidence: 99%
“…This has been recognized in several studies for example, refs. [118,131]. Prediction of water positions and mobilities in ligand complexes can be made using molecular dynamics [131], although this has only rarely been been used to date for GQ systems [132].…”
mentioning
confidence: 99%
See 1 more Smart Citation